El ambiente socio-economico de la produccion de raices y tuberculos: implicaciones para el diagnostico - Janssen, W. (International Center for Tropical Agriculture, 1989)
Using the farm as unit of analysis, diagnosis processes aimed at improving production systems are reviewed. Within a country, diagnosis should be conducted at different hierarchical levels: local (interaction between the production system and the input distribution sector, the marketing sector, possible forms of processing, and consumption characteristics); regional (appropriate selection of target site); and national (development trends and governmental policies at the macroeconomic and sectorial levels). Governmental goals common to developing countries are listed as well as several means to achieve them. Macroeconomic trends that could affect the feasibility of production systems studies are analyzed, namely growth of income per capita, urbanization, improved infrastructure and transportation, industrialization, and availability of domestic and foreign capital. The importance of having access to in-depth knowledge of the region is highlighted. The region is selected on the basis of two criteria, the technical and economic feasibility of the project and the expected distributive impact, as illustrated by the projects to improve cassava marketing, carried out on Colombia's Atlantic Coast. Local socioeconomic factors that could affect possible research and development projects are also analyzed. The importance of comprehending the different interacting components of the production system is highlighted; these include the relationship between supply and demand, the relationship between sales and self- consumption, margins of commercialization and their stability, capacity of the marketing system to absorb increasing amounts, influence of the market on production quality and timing, integration between processing and production, and inputs. The interaction between socioeconomic and agronomic problems is emphasized. (CIAT)